2017
DOI: 10.1111/1742-6723.12854
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ladder‐related falls on the emergency department and recommendations for ladder safety

Abstract: Ladder-related falls carry a considerable burden to the ED. Recommendations include ladder safety interventions that target ladder users most at risk of falls: men, ≥50 years old and performing domestic tasks. Safety interventions should emphasise task avoidance, education and training, utilisation of safety equipment and appropriate ladder setup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(45 citation statements)
references
References 21 publications
(60 reference statements)
7
37
0
Order By: Relevance
“…High falls accounted for 17% of all cases of TSCI, nearly half of which were from a ladder or roof. The incidence of ladder falls is increasing, and interventions that encourage avoiding risk, using safety equipment, and improving ladder setup have been recommended …”
Section: Discussionmentioning
confidence: 99%
“…High falls accounted for 17% of all cases of TSCI, nearly half of which were from a ladder or roof. The incidence of ladder falls is increasing, and interventions that encourage avoiding risk, using safety equipment, and improving ladder setup have been recommended …”
Section: Discussionmentioning
confidence: 99%
“…This study [1] found older adults who use ladders in non-occupational settings such as the home are the highest risk group for injury from a ladder fall which has been a similar finding in other studies [2,3]. Studies have shown simple safety measures such as setting up and stabilising the ladder correctly, wearing appropriate footwear and not overreaching on the ladder are not being practiced in the home setting [1][2][3]. Previous research has focused on the incidence of these falls and immediate patient outcomes [2,[4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 87%
“…Ladder-related falls are a frequently preventable burden of injury. The rate of ladder-related falls is increasing with many patients presenting to emergency departments (EDs) with serious injuries [1,2]. We have previously published a paper where a customised questionnaire to was used to establish the characteristics of the participants who experienced a ladder-related fall and the impact of these falls in the ED [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations